The Level of Knowledge of Dental Students and Compliance With Using Personal Protective Equipment - Kusumastiti, Anisa Ramadhani; Soaresa , Idalina Da Costa; Khafid, Mohammad; Rohmaniar, Puspa Dila; Falihan , Muhammad Akmal (Poltekkes Kemenkes Yogyakarta, 2024)
Background: Nosocomial infections or Healthcare-Associated Infections (HAIs) are infections that occur in hospitals and attack patients undergoing treatment. Dental professional student as health workers who are very vulnerable to the spread of cross- infection, so they need to understand the importance of using personal protective equipment as a first step in prevention. Objectives: This study aims to determine the correlation between the level of knowledge of Dental Professional Students on compliance with using personal protective equipment (PPE) at Dental and Oral Hospital Bhakti Wiyata Institute of Health Science Kediri. Methods: This study is a type of analytical observational research with a cross sectional design. The data obtained, processed, analyzed, and interpreted to test the hypothesis using the chi square test are presented in table form with variable data scales are ordinal and nominal. Results: The significance value of chi square in the data is 0.001 Asymp. Sig. (2- tailed). A p value of < 0.05 means that there is a significant relationship. Conclusion: There is a correlation between the level of knowledge of dental professional students on compliance with using PPE at Dental and Oral Hospital Bhakti Wiyata Institute of Health Science Kediri